Dificultades de aprendizaje de las matemáticas en estudiantes del quinto grado para proponer pautas de enseñanza psicopedagógicas de las matemáticas a los docentes de educación básica de la Unidad Educativa Pio Jaramillo Alvarado, 2021-2022 - Carrión Medina, Cristina Alejandra (2023)
The objective of this research was to determine the learning difficulties of mathematics in fifth grade students of Basic General Education; It was a study with a quantitative approach, descriptive type, non-experimental and cross-sectional design; A survey was applied to the teachers, and the Evalúa-4 battery was applied to the 26 students in the sample. The results of the survey indicate that 66.7% of teachers consider that mathematical learning problems are related to difficulties in problem solving; On the other hand, according to the Evalúa-4 battery, 88.5% of the students in the Calculation and Numeration test obtained a percentile score between 0 and 19, placing themselves at a low level; and in the problem solving test, 53.8% obtained a percentile score between 0 and 19, reaching a low level. From these results it is concluded that teachers think that mathematical learning problems are due to difficulties in solving problems as well as it is concluded that students present low levels with respect to mathematical learning, related to calculation and numeration and resolution. Of problems, for this reason psycho-pedagogical guidelines are presented to optimize or improve the academic performance of students. Keywords: learning, battery, evaluate, mathematical, psycho-pedagogical guidelines.